Estrategia psicopedagógica para el manejo del estrés académico en estudiantes de tercero de bachillerato en la Unidad Educativa Réplica Nicolás Infante Díaz. - Salazar Quiñonez, Jennifer Stefania (2025)
Academic stress negatively impacts students' development in various personal, social, and cognitive contexts, which is why it is necessary to strengthen and build coping strategies for stressful situations. Given the above, this research focused on creating a strategy for managing academic stress in third-year high school students at the Nicolás Infante Díaz Educational Unit, which is based on theories related to the study variables. The strategy was evaluated to verify that it fulfilled its initial purpose. On the other hand, the methodology had a descriptive qualitative approach, the population was third-year high school students, and there were four participants, selected by convenience criteria. In addition, the instrument used was a semi-structured interview directed at the students participating in this study. And, the results evidenced the triggering needs of academic stress in the participants for which it is necessary to strengthen the strategies that use, but which do not have long-term results preventing prolong an adequate management of academic stress. Therefore, it is concluded that the proposed strategy meets the criteria of clarity, relevance and feasibility and is directed with positive approaches related to theories and, at the same time can be applied at the time in order to help students to have a good development in the different areas that make them up and also in their learning process.